2018
DOI: 10.1017/s2040174418000454
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early postnatal nutrition on chronic kidney disease and arterial hypertension in adulthood: a narrative review

Abstract: Intrauterine growth restriction (IUGR) has been identified as a risk factor for adult chronic kidney disease (CKD), including hypertension (HTN). Accelerated postnatal catch-up growth superimposed to IUGR has been shown to further increase the risk of CKD and HTN. Although the impact of excessive postnatal growth without previous IUGR is less clear, excessive postnatal overfeeding in experimental animals shows a strong impact on the risk of CKD and HTN in adulthood. On the other hand, food restriction in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 120 publications
(232 reference statements)
0
6
0
Order By: Relevance
“…We initially hypothesised that low podocyte endowment may be an important mechanism that leads to the onset of podocyte-associated glomerular pathology later in life. However, our findings suggest that LPD offspring with low nephron endowment and a 9% lower podocyte endowment at 6 months do not develop significant albuminuria or glomerulosclerosis despite accelerated early postnatal growth (catch-up growth), a known risk factor for renal disease and hypertension (16). This may be due in part to their still smaller body size (despite significant catch-up growth) and/or with the timing of our analysis, given that 6 months is a relatively young age in rats (48).…”
Section: Discussionmentioning
confidence: 63%
“…We initially hypothesised that low podocyte endowment may be an important mechanism that leads to the onset of podocyte-associated glomerular pathology later in life. However, our findings suggest that LPD offspring with low nephron endowment and a 9% lower podocyte endowment at 6 months do not develop significant albuminuria or glomerulosclerosis despite accelerated early postnatal growth (catch-up growth), a known risk factor for renal disease and hypertension (16). This may be due in part to their still smaller body size (despite significant catch-up growth) and/or with the timing of our analysis, given that 6 months is a relatively young age in rats (48).…”
Section: Discussionmentioning
confidence: 63%
“…Caroline Abitbol et al in Miami found a link between the appearance of proteinuria and its subsequent increase, as measured by the protein/creatinine ratio in urine, and a subsequent deterioration of glomerular filtration ( r = 0.8, p = 0.0001) and a tendency toward obesity with a body mass index (BMI) greater than the 85th percentile (89 percent sensitivity, PPV: 67%, p = 0.03) in newborns under 1,000 g. A subsequent study by the same center looked at the effects of obesity and prematurity on renal disease progression in a retrospective cohort of these children (44 obese and 36 non-obese). When compared to obese children born at term, patients who became obese after being born extremely preterm had a higher risk of impaired kidney function during childhood (hazard ratio 2.4; 95% CI: 1.1–7.1; p = 0.04) ( 60 ).…”
Section: Impact Of Lbw In Pediatrics and Obstetricsmentioning
confidence: 99%
“…Indeed, recent studies have highlighted the potential role of intrauterine growth restriction (IUGR) in the pathophysiology of psychiatric neurodevelopment diseases, such as SZ [17][18][19]. IUGR [20] is widely considered to be a predisposing factor to several non-transmissible diseases such as cardiovascular and renal disorders [21][22][23]. In addition to significantly impacting birth weight [20,24], IUGR has also been correlated with impaired cerebral development [20,25,26] and adverse cognitive outcomes, such as lower IQ and reduced working memory [24,27], occurring even many years after the adverse environmental exposure.…”
Section: Introductionmentioning
confidence: 99%